Inflammation‐Induced Long Intergenic Noncoding RNA (LINC00665) Increases Malignancy Through Activating the Double‐Stranded RNA–Activated Protein Kinase/Nuclear Factor Kappa B Pathway in Hepatocellular Carcinoma. Issue 5 (19th October 2020) - Ding, Jie; Zhao, Jingjing; Huan, Lin; Liu, Yizhe; Qiao, Yejun; Wang, Zhen; Chen, Zhiao; Huang, Shenglin; Zhao, Yingjun; He, Xianghuo
Abstract : Background and Aims: The nuclear factor kappa B (NF‐κB) signaling pathway is important for linking inflammation and tumorigenesis. Here, we characterized an NF‐κB signaling activation–induced long intergenic noncoding (LINC) RNA in hepatocellular carcinoma (HCC), LINC00665, that contributes to the enhanced cell proliferation of HCC cells both in vitro and in vivo . Approach and Results: LINC00665 physically interacts with the double‐stranded RNA (dsRNA)‐activated protein kinase (PKR), enhances its activation, and maintains its protein stability by blocking ubiquitin/proteasome‐dependent degradation, resulting in a positive feedback regulation of NF‐κB signaling in HCC cells. Notably, patients with HCC and higher LINC00665 have poorer outcomes in the clinic. Conclusions: Our findings indicate that LINC00665 is involved in the NF‐κB signaling activation in HCC cells and that the inflammatory LINC00665/PKR/NF‐κB loop plays important oncogenic roles in hepatic cancer progression and may be a potential therapeutic target.